Population dynamics of four insect defoliators in a dryland South Island Eucalyptus plantation - Lin, H.; Murray, T.J.; Mason, E.G. (New Zealand Plant Protection, 2016)
Exotic insect defoliators originally from Australia are present in New Zealand Eucalyptus plantations Pest outbreaks causing significant defoliation can reduce tree growth and productivity There is limited information on the population dynamics of major Eucalyptus defoliators in the South Island Populations of four defoliators were monitored monthly from November 2015 to March 2016 in a dryland Eucalyptus plantation in Marlborough by assessing 35 shoots from each of 225 trees Only one generation of Paropsis charybdis was observed Peak adult abundance was in December/January and adults disappeared in March This is different from North Island and Australian studies in which two generations are often observed Opodiphthera eucalypti had two distinct generations with larval populations peaking in December and February/March Most Phylacteophaga froggatti larvae were found after December but populations were relatively low throughout the monitoring period Strepsicrates macropetana reached peak larval abundance in February and had multiple overlapping generations These results suggest differences in the population dynamics of eucalypt defoliators in the South Island compared to those reported in the North Differences are likely due to local environmental conditions which were notably dry during this particular monitoring season These data provide important information for pest management in South Island dryland Eucalyptus plantations